AKURASI FOOD RECALL DAN FOOD RECORD DALAM AKURASI SIMPLIFIED DIETASI ASSESSMENT (SDA) PADA ANAK USIA SEKOLAH UNTUK IDENTIFIKASI RESIKO KURANG VITAMIN A - Nawangwulan Widyastuti (Politeknik Pembangunan Pertanian Bogor, 2020)
A simplified dietary assessment method using food consumption approach to identify thevulnerable group vitamin A deficiency was developed by IVACG (International Vitamin AConsultative Group). For food comsumption survey, food weighing, food recall and food recordwere coomonly used. The objective of this research was to analyze the accuration of food recalland food record using simplified dietary assessment on school children to identify vitamin Arisk. The study showed that vitamin A food pattern’s of school children mostly was fromvegetables and eggs, although the quantity was very low. Fruit was consumed infequently withthe low quantity. Vitamin A consumption using food recall tend to underestimate, while foodrecord tend to overestimate compare with food weighing. Comparing with vitamin A RDA, theRDA level was below 65% of RDA. The prevalence of sample with vitamin A risk was higher onfood recall (64.7%) and lower on food record (60.0%) compare with food weighing (62.4%)with the smallest deviance toward food weighing was found on food record. The sensitivity offood recall was higher than food record, although the difference was not to high. The specificityand positive predicted value of food recall was lower than food record. Food record had betteraccuration than food recall in identifying vitamin A risk. The influenced factors of vitamin Arisk was family’s income, family size and vitamin/supplement feeding.